Implementasi Kurikulum Merdeka Belajar pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Fase B di SD Negeri 358 Pengkasalu Kabupaten Luwu - Anita, Anita; Yusuf, Munir; Zuljalal Al Hamdany, Muhammad (South Sulawesi Education Development, 2024)
This thesis discusses the implementation of the Independent Learning Curriculum in Phase B Islamic Religious Education Learning at SD Negeri 358 Pengkasalu, Luwu Regency. This research aims: 1) To determine the implementation of the independent learning curriculum in Phase B Islamic religious education and morals lessons at SD Negeri 358 Pengkasalu, 2) To determine the supporting factors and inhibiting factors of the Independent curriculum in Islamic religious and moral education lessons at state elementary schools 358 Pengkasalu. This research uses a descriptive qualitative approach. The research subjects were school principals, PAI teachers, class IV homeroom teachers, staff and students. Data collection was carried out through observation, interviews and documentation. Meanwhile, the data analysis used in the research is data reduction, data presentation, and drawing conclusions. Meanwhile, data validity testing uses data source triangulation and technical triangulation. The research results show that SD Negeri 358 Pengkasalu has implemented the Merdeka curriculum since the 2022/2023 academic year. Implementation of the Merdeka curriculum in the classroom goes through three stages, namely 1) planning stage, namely analyzing CP, TP, ATP and teaching modules, 2) implementation stage, namely learning that is oriented towards learning outcomes, 3) evaluation stage, namely formative assessment and summative assessment. Supporting factors for implementing the Merdeka curriculum are adequate facilities and infrastructure. Meanwhile, the inhibiting factors in implementing the Merdeka curriculum are students who are less active in class and do not understand learning. Keywords: Independent Learning Curriculum, Islamic Religious Education Learning